Ceramic materials in civil construction: a brief review (Research, Society and Development, 2019)
Nowadays, in the civil construction sector several pathological manifestations that affect the buildings are reported, among them of high relevance those related to the ceramic coverings. Although they are not directly related to the safety of the structure, they are always cause of damages to the owners due to the aesthetic damages caused to the buildings, their appearance can be related to the phases of production, design or application of the ceramic coating. These manifestations may occur mainly in the form of patches, cracks, fissures, cracking and detachment of the coating. This work exposes in a practical way some pathologies that cause these damages in the coatings, analyzing examples of cases in which the appearance of pathological manifestations can be observed.